2021
DOI: 10.3389/fimmu.2020.605231
|View full text |Cite
|
Sign up to set email alerts
|

Developing a 3D B Cell Lymphoma Culture System to Model Antibody Therapy

Abstract: Diffuse large cell B cell lymphoma (DLBCL) accounts for approximately 30%–40% of all non-Hodgkin lymphoma (NHL) cases. Current first line DLBCL treatment results in long-term remission in more than 60% of cases. However, those patients with primary refractory disease or early relapse exhibit poor prognosis, highlighting a requirement for alternative therapies. Our aim was to develop a novel model of DLBCL that facilitates in vitro testing of current and novel therapies by replicating key components of the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
(70 reference statements)
0
20
0
Order By: Relevance
“… 35 Recently, Foxall et al described a collagen scaffolds-based spheroid co-culture system comprising DLBCL cells, cancer-associated fibroblasts (CAF), and tumor-associated macrophages (TAM). 36 Notably, both studies demonstrated that DLBCL cells interact with their constituent components, resulting in their improved viability compared to 2D mono-cultures. Finally, An et al successfully developed a canine 3D hybrid model by co-culturing the lymphoma cells, and lymph node-derived primary stromal cells.…”
Section: Introductionmentioning
confidence: 98%
“… 35 Recently, Foxall et al described a collagen scaffolds-based spheroid co-culture system comprising DLBCL cells, cancer-associated fibroblasts (CAF), and tumor-associated macrophages (TAM). 36 Notably, both studies demonstrated that DLBCL cells interact with their constituent components, resulting in their improved viability compared to 2D mono-cultures. Finally, An et al successfully developed a canine 3D hybrid model by co-culturing the lymphoma cells, and lymph node-derived primary stromal cells.…”
Section: Introductionmentioning
confidence: 98%
“… 20 However, modeling the interactions of the TME with primary lymphoma B cells in 3D cocultures remains a challenge. In particular, 3D cocultures have been successful only with primary DLBCL cells 21 but not with primary FL cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the importance of developing more reliable in vitro systems taking into account the complex reciprocal interactions occurring in vivo between malignant and non-malignant cells is evident. Recently, some platforms prepared the groundwork for the investigation of novel agents (e.g., immunotherapeutic antibodies) aimed at targeting the key cellular components of the TME (e.g., CAFs or TAMs) in a clinically relevant context [ 173 ].…”
Section: Three-dimensional Culture Models: Moving From Spheroids To N...mentioning
confidence: 99%